Ketegasan Pendidik dalam Pemberian Sanksi Bagi Peserta Didik di MAN 1 Buol Provinsi Sulawesi Tengah - A. Haruna, Ruqiya; Yahiji, Kasim; Rakhmawati (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the firmness of educators in giving sanctions to students at MAN 1 Buol, this study also aims to ensure tthat the giving of sanctions continues to prioritize educational principles, in accordance with government regulations and the code of ethics of educators, and involves good communication between educators, parents and students. The research method used in this study is a secriptive qualitative method with a field approach to describe the phenomenon in depth. Date were collected through observation and interview, with five educators and five students, and using documentation related to the research. The results of the study showed that the firmness of educators in giving sanctions includes three aspects: enforcement of rules, self control, and creation of a harmonious atmosphere. Sanctions are given in stages, starting from light sanctions (verbal warnings, confiscation of goods), moderate sanctions (calling parents, statement letters), to severe sanctions (suspension or expulsion from School). The impact of the firmness of giving sanctions is an increase in student discipline, although it is necessary to be aware of the sanctions given are not in accordance with the rules set, such as trauma from students.